2018
DOI: 10.21037/tcr.2018.11.07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and predictive factors analyses for patient-self-reported depression, anxiety and quality of life in patients with metastatic renal cell carcinoma underwent interferon-α treatment: a prospective cohort study

Abstract: Background: This study aimed to investigate the patient-self-reported depression, anxiety and quality of life (QoL) as well as their predictive factors in patients with metastatic renal cell carcinoma (mRCC) underwent interferon-alpha (IFN-α) treatment.Methods: A total of 127 patients with mRCC underwent IFN-α treatment were consecutively enrolled in this prospective cohort study. Anxiety, depression and QoL were assessed at week 0 (W0), W4, W8 and W12 by Hospital Anxiety and Depression Scale (HADS) and Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Three studies investigated the impact of psychological distress, anxiety and/or depression, on patients with metastatic RCC. Two studies included 304 patients from the US [ 29 , 30 ] and one included 127 patients from China [ 31 ]. Different instruments were used to measure distress, anxiety and/or depression including a touch screen-based instrument— either HADS or CES-D. A meta-analysis was not performed due to heterogeneity between studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies investigated the impact of psychological distress, anxiety and/or depression, on patients with metastatic RCC. Two studies included 304 patients from the US [ 29 , 30 ] and one included 127 patients from China [ 31 ]. Different instruments were used to measure distress, anxiety and/or depression including a touch screen-based instrument— either HADS or CES-D. A meta-analysis was not performed due to heterogeneity between studies.…”
Section: Resultsmentioning
confidence: 99%
“…), but statistical significance was not reached. In a prospective evaluation of a Chinese cohort, Wang et al [ 31 ] reported that, in patients with metastatic RCC, anxiety and depression increased 3 months after interferon-α treatment ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Depression is a serious life-threatening disorder that affects hundreds of millions of patients and may occur suddenly at all ages (1). This severe psychiatric disorder is the 4th leading cause of disability worldwide, which should be looked at more seriously, and it has a prevalence of above 15% (2). Depression is not a single disorder, but a heterogeneous syndrome which comprises of several symptoms of distinct causes and pathophysiology (3).…”
Section: Introductionmentioning
confidence: 99%
“…No significant changes were observed in patients on surveillance, suggesting that AS is well tolerated over time despite the probable progression in some of such patients. To compare, in one series of patients with mRCC receiving ST, 31% had depression prior to starting ST, which increased to 43% after 12 weeks of therapy (43). risk patients, these patients are probably be good AS candidates.…”
Section: Quality Of Lifementioning
confidence: 99%